Pengaruh Coaching, Mentoring, dan Coworker Support Terhadap Job Performance Pada Pegawai PT. Pegadaian (Persero) Cabang Nganjuk - Lalitaratri, Titah (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to examine how coaching, mentoring, and coworker support affect employee job performance. Data were collected from 40 employees of PT. Pegadaian (Persero) Nganjuk Branch using 37 statement items with quantitative methods. IBM SPSS 26 was used for data analysis. Likert scale was used as the measurement scale. The results showed that coaching has a positive and significant effect on job performance, mentoring has a positive and significant effect on job performance, and coworker support has a positive and significant effect on job performance.